The organisation (re)invented by its blogs. (1st January 2013) - Primo, Alex; Zago, Gabriela
This article discusses how interactions in organisational blogs participate in the emergence of the organisation itself. Based on the principles of The Montreal School of Organisational Communication, the paper reflects on how the recursive relationship between texts and conversations in blogs mobilises the organisation and contributes to its continuing creation. In order to conduct this argument, the concept of social media, uses of organisational blogs and the main contributions of The Montreal School are analysed. Finally, by discussing examples of four genres of organisational blogs, we demonstrate how they contribute to the definition of the organisation. Beyond their promotional potential, the blog's role as co-creator of the organisation is highlighted.